The natural history of pollination - Proctor, Michael; Yeo, Peter 1929-; Lack, Andrew (Timber Press, 1996)
This is a brand new, fully updated edition of the natural history classic first published in 1973 as The Pollination of Flowers. The importance of insects in pollinating flowers is today so well known it is easy to forget that it was discovered little more than two centuries ago: before that, it was believed that the concern of bees with flowers was simply a matter of collecting honey. But the methods by which pollen reaches the female flower, enabling fertilisation and seed production to take place, include some of the most varied and fascinating mechanisms in the natural world. The Natural History of Pollination describes all the ways in which pollination is brought about: by wind, water, birds, bats and even mice and rats; but principally by a great diversity of insects in an amazing range of ways, some simple, some bizarre. This book is a unique introduction to a complex yet easily accessible subject of great fascination.
Keywords: Bestuiving; Plant-dier-relatie; Pollination; Bestäubung